ANALISIS SOSIO-EKOLOGIS EKOSISTEM LAMUN DI TAMAN NASIONAL LAUT KEPULAUAN SERIBU - , Aynuddin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Seagrass, as a part of the coastal ecosystem, are very unique due to their distinct adaptation to the submarine environment. Despite their limited diversity, seagrass support vast variety of life and play important socio-ecological role to coastal area. Objectives of this study are: (1) to know the condition and status of seagrass ecosystem, (2) to study human exploitation activities and threats on seagrass ecosystem, and (3) to analize management of seagrass ecosystem. Study was conducted on March 2014 at four islands in settlement zone of Kepulauan Seribu Marine National Park (Panggang, Pramuka, Kelapa, and Harapan island). Social data was obtained from semi-structured interview from snowball sampling design, meanwhile seagrass data was obtained from quadratic transect method. Study result shows that seagrass species in Kepulauan Seribu Marine National Park consist of 2-7 species with 58,9 shoot/m2 density and mainly in damaged status (percent cover <30%). Interview data shows that seagrass ecosystem have being part of societyâs life from early time (ngoyok, tegur net, and marineculture). Nevertheless, there are lack of peopleâs knowledge about this ecosystem. The main threat to this ecosystem sustainability are sand exploitation, and also dredging and burial as part of area development in reef flat. Seagrass ecosystem management based on balanced use and conservation is an appropriate concept considering the ecosystem and societyâs condition now.